Inborn errors of metabolism and osteopetrosis - Fernandes, Juliana Folloni; Rodrigues, Adriana Melo; Daudt, Liane Esteves; Klinger, Paulo; Bonfim, Carmem (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Allogeneic hematopoietic cell transplantation (HCT) remains the standard and potentially curative therapy for certain inborn errors of metabolism (IEM) and for osteopetrosis. This paper updates the Brazilian consensus guidelines for HCT indications in pediatric patients with IEM, specifically focusing on mucopolysaccharidosis, X-linked adrenoleukodystrophy, Krabbe disease, metachromatic leukodystrophy, and osteopetrosis. We emphasize the importance of early diagnosis, timely referral, and multidisciplinary follow-up to optimize patient outcomes. Additionally, we discuss the evolving landscape of conditioning regimens and donor selection criteria, underscoring the critical need for genetic testing to guide therapy. Future directions in research, including gene therapy and novel therapeutic strategies, are also highlighted.